2022
DOI: 10.1109/ted.2022.3198035
|View full text |Cite
|
Sign up to set email alerts
|

A Self-Sustained Mass Sensor With Physical Closed Loop Based on Thermal-Piezoresistive Coupled Resonators

Abstract: This article reports a mode-localized mass 1 sensor based on thermal-actuation piezoresistive-detection 2 self-oscillated weakly coupled resonators. Detailed theo-3 retical models and simulations of the self-oscillation of 4 the coupled resonators were established and were also 5 verified using optical and electrical measurements. The sen-6 sor was fabricated and characterized in terms of stability, 7 linearity, sensitivity, and resolution. Supplied with only a 8 constant direct current (DC), the resonant mass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Since the first miniature Si piezoresistive heat engine was reported in 2011 [1], a variety of self-sustained thermal-piezoresistive resonators or oscillators have been developed for mass sensing [2,3], Lorentz force measurement [4], gas detection [5], and signal amplification [6]. It was demonstrated that the thermalpiezoresistive effect is strong enough to initiate and maintain the mechanical oscillation of the resonator driven by direct current (DC), without the demand for any external alternating current (AC) source and amplifying circuitry.…”
Section: Introductionmentioning
confidence: 99%
“…Since the first miniature Si piezoresistive heat engine was reported in 2011 [1], a variety of self-sustained thermal-piezoresistive resonators or oscillators have been developed for mass sensing [2,3], Lorentz force measurement [4], gas detection [5], and signal amplification [6]. It was demonstrated that the thermalpiezoresistive effect is strong enough to initiate and maintain the mechanical oscillation of the resonator driven by direct current (DC), without the demand for any external alternating current (AC) source and amplifying circuitry.…”
Section: Introductionmentioning
confidence: 99%